Analyzing the Effect of Digital Marketing Strategies on Consumer Buying Behavior in Fashion Retail after the COVID-19 Pandemic - Bambang Setiawan; Rizky Aditya Putra (Mustard Journal De Ecobusin, 2025)
This study analyzes the influence of digital marketing strategies on consumer purchasing decisions in fashion retail businesses in the post-pandemic era, focusing on identifying which elements of digital strategies significantly affect consumer decision-making. Using a quantitative explanatory approach, data were collected from 150 respondents who had purchased fashion products online in the past year through a Google Form-based questionnaire, with six variables examined: social media content, online advertising, influencer marketing, interactive websites, email marketing, and digital promotions. Multiple linear regression analysis supported by validity and reliability tests revealed that digital marketing strategies significantly influence purchasing decisions (p < 0.01), with digital promotions, social media content, influencer marketing, and online advertising showing significant effects, while interactive websites and email marketing did not. The adjusted R² value of 0.661 indicates that 66.1% of the variation in purchasing decisions is explained by the strategies employed. The study concludes that digital marketing strategies play a crucial role in shaping consumer purchasing behavior in fashion retail, and businesses should prioritize social media, digital promotions, and influencer collaborations to effectively increase purchase conversions.